Risk factors for and characteristics of community‐ and hospital‐acquired drug‐induced acute kidney injuries. (25th January 2022) - Rey, Amayelle; Gras‐Champel, Valérie; Choukroun, Gabriel; Masmoudi, Kamel; Liabeuf, Sophie
Abstract: Drugs constitute one of the leading causes of acute kidney injuries (AKIs) and can appear in community (CA‐AKI) or hospital (HA‐AKI) population. The objectives of the present study of a cohort of hospitalized patients with AKI were to describe the characteristics of drug‐induced AKIs and the patients' short‐term outcomes and assess risk factors for drug‐induced AKIs overall, CA‐AKIs, and HA‐AKIs. Based on a cohort of 1557 hospitalized patients suffering from AKIs based on PMSI extraction and chart review (IRA‐PMSI), drug‐induced AKIs were identified by applying the Naranjo adverse drug reaction (ADR) probability scale. Multivariate logistic regression was used to identify factors associated with CA‐AKIs and/or HA‐AKIs. When considering the 1557 patients who experienced an AKI, 445 (28.6%) of the injuries were drug‐induced (180 CA‐AKIs (40.4%) and 265 HA‐AKIs (59.6%)). Antibiotics, diuretics, and contrast agents were significantly more likely to be involved in HA‐AKIs, whereas antineoplastic, lipid‐lowering drugs, antidiabetics, and immunosuppressive were significantly more likely to be involved in CA‐AKIs. Female sex (odds ratio [OR] [95%CI] = 1.3 [1.04–1.67]), chronic kidney disease (CKD) (OR = 1.8 [1.40–2.67]), and a history of ADRs of any type (OR = 1.3 [1.05–1.73]) were significant risk factors for drug‐induced AKIs. CKD was a risk factor for both CA‐AKI and HA‐AKI. In view of the long‐term impact of AKI on the kidneys and the differences between our CA‐AKI and HA‐AKI subgroups, our present results are interesting for optimizing treatments, limiting the occurrence of CA‐ and HA‐AKIs and (ultimately) reducing healthcare costs.